Data Governance and Policy in Africa - Ndemo, Bitange; Ndung'u, Njuguna; Odhiambo, Scholastica; Shimeles, Abebe (Information Technology and Global Governance, 2023)
This open access book examines data governance and its implications for policymaking in Africa. Bringing together economists, lawyers, statisticians, and technology experts, it assesses gaps in both the availability and use of existing data across the continent, and argues that data creation, management and governance need to improve if private and public sectors are to reap the benefits of big data and digital technologies. It also considers lessons from across the globe to assess principles, norms and practices that can guide the development of data governance in Africa. The book will appeal to scholars and students of data governance, technology and public policy, as well as practitioners and policy makers. Bitange Ndemo is the Kenyan Ambassador to Belgium and the European Union Mission. He was previously Professor of Entrepreneurship at the University of Nairobi, Kenya. Njuguna Ndung'u is Associate Professor of Economics at the University of Nairobi. He is the Cabinet Secretary of the National Treasury of Kenya, a former Governor of the Central Bank of Kenya, and Executive Director at the African Economic Research Consortium. Scholastica Odhiambo is Manager of Research at the African Economic Research Consortium. She was previously Senior Lecturer of Economics at Maseno University, Kenya. Abebe Shimeles is Honorary Professor of Economics at the University of Cape Town, South Africa. He formerly served as Director of Research at the African Economic Research Consortium. .